Peningkatan Kemampuan Pemahaman dan Penalaran Matematis Siswa melalui Metode Penemuan Terbimbing di SMP YPPU Sigli - Zakaria Zakaria (Universitas Syiah Kuala, 2014)
This study aims to look at the differences increase understanding and mathematical reasoning abilities among students who were taught by the guided discovery method with students taught by conventional methods. Formulation of the problem in this research are: 1) does increased understanding and mathematical reasoning abilities that students acquire learning by using guided discovery method is better than students who received conventional learning is reviewed based on: a) the whole student, b) the level of students' mathematical ability (high, medium, and low)?; 2) Is there an interaction between factors of learning methods and levels of understanding of students' mathematical ability to increase understanding of mathematical or mathematical reasoning?; 3) Is there a positive correlation between increased capacity and improved mathematical understanding of mathematical reasoning ability in learning by using guided discovery method? This type of research is a quantitative study using a pretest- posttest with control group design. The experiment was conducted in YPPU, Junior High School Sigli, Aceh with the number of students of 60 people consisting of two classes of experimental classes to acquire learning and control methods of guided discovery learning classes to obtain by conventional methods. Collecting data using a test for the ability of mathematical understanding and mathematical reasoning abilities. Processing the data using the t test and two-ways ANOVA with SPSS 17.0 with significance level = 0.05. Based on the analysis of data it can be concluded that increasing the understanding and mathematical reasoning abilities of students who obtained with the method of guided discovery learning is better than learning by students who received conventional methods are reviewed based on the whole student and based on the level of the student. There is no interaction between the factors and the level of students' learning methods to increase understanding or mathematical reasoning ability. Testing correlation indicates that there is a strong positive correlation of 0.708 between increased understanding and mathematical reasoning abilities in students being taught by using guided discovery method